2018
DOI: 10.1039/c7cp08292d
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and heterogeneous dynamics in native and denatured bovine serum albumin

Abstract: A characteristic property of unfolded and disordered proteins is their high molecular flexibility, which enables the exploration of a large conformational space. We present neutron scattering experiments on the dynamics of denatured and native folded bovine serum albumin (BSA) in solution. Global protein diffusion and internal macromolecular dynamics were measured using quasielastic neutron time-of-flight and backscattering spectroscopy on the picosecond to nanosecond time- and Ångstrom length-scale. Internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 62 publications
6
26
0
Order By: Relevance
“…By considering the short-time range probed by QENS, our results indicated that hydrodynamic interactions of Hb in concentrated solutions were stronger than predicted from the theory for simple colloidal hard-sphere suspensions; this predicted a value of H = 1 − 1.831ϕ = 0.63 for a volume fraction of ϕ = 0.20 being equivalent to the QENS RBC lysate sample [61]. This result was in agreement with previous reports on globular, multi-domain and intrinsically disordered proteins [5,59,[62][63][64][65].…”
Section: Interpretation Of Qens Data On Global Hb Diffusionsupporting
confidence: 91%
“…By considering the short-time range probed by QENS, our results indicated that hydrodynamic interactions of Hb in concentrated solutions were stronger than predicted from the theory for simple colloidal hard-sphere suspensions; this predicted a value of H = 1 − 1.831ϕ = 0.63 for a volume fraction of ϕ = 0.20 being equivalent to the QENS RBC lysate sample [61]. This result was in agreement with previous reports on globular, multi-domain and intrinsically disordered proteins [5,59,[62][63][64][65].…”
Section: Interpretation Of Qens Data On Global Hb Diffusionsupporting
confidence: 91%
“…However, a later NSE study by Ameseder et al (2018a) indicated that presence of the sulfur bonds leads to a suppression of low-frequency Zimm modes (see section 'Relations of protein dynamics to structure: from globular to intrinsically disordered proteins'). Although incapable of distinguishing heterogeneous dynamics on the same timescale, as the authors noted (Ameseder et al, 2018b), the Brownian oscillator model yielded reasonably similar results with D fast int = 95.8 + 1.8 Å 2 ns −1 and D slow int = 24.5 + 1.5 Å 2 ns −1 in the native protein and diffusion coefficients between 14 and 21 Å 2 ns −1 in denatured BSA. As remarked by Ameseder and collaborators, D fast int and D slow int obtained with this model are on the same order of magnitude as the diffusion coefficients obtained from the switching model applied before on BSA at the same temperature (Grimaldo et al, 2015a) and D fast int is in good agreement with a 'slow' dynamics of amino acid side-chains in folded proteins observed by Monkenbusch et al (2015) and characterized by effective diffusion coefficients of around 70-80 Å 2 ns −1 (Ameseder et al, 2018b) (see also section 'Combination of neutron spectroscopy techniques: alcohol dehydrogenase').…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Anmentioning
confidence: 62%
“…The apparent disappearance of the fast dynamics upon denaturation is to be interpreted together with the drastic increase of the fraction of atoms moving on both the timescales accessible by TOF and NSE, respectively, as obtained from the Brownian oscillator model. As suggested by Ameseder et al (2018b), in the denatured protein, the slow process may become the predominating contribution to the dynamics (e.g. if the additional mobile atoms were mostly slow), practically obscuring the faster one.…”
Section: Comparison Of Internal Protein Dynamics In Native Molten Anmentioning
confidence: 99%
See 2 more Smart Citations